Preschool Teachers' views on Sensory Education - Bartan, Saadet; Alisinanoğlu, Fatma (Southeast Asia Early Childhood Journal, 2024)
The aim of this study is to reveal preschool teachers' views on sensory education. In the study, phenomenological design, one of the qualitative research methods, was selected. The study group of the research consists of 20 preschool teachers working in a city in Turkey in the 2022-2023 academic year. Maximum diversity sampling, one of the purposeful sampling types, was used to form the study group. A semi-structured interview form consisting of open-ended questions was used as a data collection tool. The data were analyzed using content analysis technique. As a result of the research, it was seen that preschool teachers had an average knowledge about sensory education It was determined that they carried out studies for the senses in all activities. Most of the participants stated that they did not have enough materials for the implementation of sensory education and that the physical conditions of their classrooms and schools were unfavourable. Sensory education supports children's developmental areas, family participation, physical and material equipment of the classroom and school are important in this process. It was concluded that pre-school teachers did not fully master the concept of sensation, but the benefits of sensory education and its contribution to children's developmental areas are important. according to research results; n-service trainings can be organised for teachers about sensory education and its importance in early childhood, occupational therapist support can be provided to pre-school institutions by working interdisciplinary at the point of sensory education and classrooms and schools can be supported in terms of sensory education materials, can be recommended.